Innes: Security Bonds - Sandri, G.; Puccia, A.; Bardi, M.; Corbari, E.; DeMarco, J. (International Journal of Criminology and Sociology, 2016)
Risk in society is a pertinent concept of late modernity. Most elements of our social and interpersonal lives are in some way linked to concerns about safety, security and fear of harm. As a consequence, we spend a great deal of time engaged in emotional, physical and economic processes that facilitate our safety. Whether this be through purchasing anti-theft devices, or subscribing to self-defense training courses; participating in neighbourhood-watch schemes or altering our behavior to prevent susceptibility to victimization, all demonstrate an inherent pre-occupation with risk and perceived danger. The work presented in this paper offers an in-depth socio-criminological analysis focusing on the issue of citizens insecurity, and proposes an original interpretative paradigm emerging from findings on the INNES (Intimate Neighborhood Strengthening) European Project. A presentation of the idiographic and nomothetic motivations and conditions influencing and predicting social fears and insecurities over the last two decades is discussed, with the presentation of the new interpretative model, ‘Social Cobweb Theory’. This model focuses on solidarity and on the strengthening of intimate neighborhood bonds and argues that these aforementioned concepts function as an effective approach in lowering citizens’ perceptions of individual insecurities and risk.